Legalitas Cover Lagu “Lagi Syantik” Pada Channel Youtube (Analisis Putusan Mahkamah Agung Nomor 910 K/Pdt.Sus-HKI/2020) - Veri Yuniarto Prabowo; Fifiana Wisnaeni (Magister Kenotariatan Universitas Diponegoro, 2023)
AbstractOften song covers on Youtube so easily changing music arrangement and genre of song work to appear as if it were theirs, without permission of songwriter. As happened in case of song covers in the Supreme Court Decision Number 910 K/Pdt.Sus-HKI/2020. This study aims to determine legality of song covers based on Copyright Law and to find out whether Judge's decision on song covers “Lagi Syantik” has fulfilled legal protection. This research uses normative legal research methods. Results of this study found that legality of song covers on social media can be referred to as fair use doctrine contained in Article 43 letter d of Copyright Law. This means that song covers on social media can be categorized as legal, if person who song covers: first, does not get commercial benefits; and second, get permission from copyright owner. In this research case study, Plaintiff is not harmed because income from song covers